The effect of service quality and brand trust on loyalty through customer satisfaction in transportation service Go-jek (go-ride) in Palembang City - Putri, Yuni Adinda; Wahab, Zakaria; Shihab, Muchsin Saggaff; Hanafi, Agustina (Universitas Muhammadiyah Pontianak, 2018)
The objective of this study to analyze the effect of service quality and brand trust onloyalty through customer satisfaction. The Go-Jek (Go-Ride) users in Palembangwere taken as respondents. This research used purposive sampling technique; thenumber respondents were collected, 100 respondents. The data analyzedby usingStructural Equation Modeling (SEM). The results of this study indicate that brandtrust does not affect consumer loyalty. The suggestions in this study that themanagement is expected to conduct a survey to determine the needs of the desiredcustomer and provide promotions related to the desired requirements.